Teacher competences for active learning in engineering education - Neves, Renato Martins (2021)
The implementation of active learning strategies in engineering education still encounters barriers when facing conventional teaching-learning practices. This work aims to contribute to the discussion on teachers' pedagogical competences required for active learning. This contribution is developed from the perceptions of 205 engineering teachers of Brazilian higher education institutions, centered on significant teaching competences necessary for teachers of engineering courses and how to develop them in the active learning context. The results show that essential competences identified by the participants are (I) teamwork (teachers' cooperation); (II) teacher-student relationships (empathy); (III) feedback about students' performance throughout the learning process; (IV) information and communication technology (ICT) competences; (V) selecting and adapting the teaching-learning methodologies to the class context; and (VI) creativity. A complementary logistic regression model suggested that female Ph.D. full-time teachers are more likely to employ active learning. Differences in active learning adoption among Brazilian regions were also captured by the model. The identified competences are essential for the sustainability of the innovation of teaching practices in the context of active learning, which may be used to inform more effective professional training of engineering teachers in the current globalized scenario.